Test setup and first report of the removal efficacy of a fruit and vegetable industrial cleaner on fresh-cut vegetables contaminated with Taenia sp. eggs - Lavallén, Carla Mariela (2025)
Food-borne disease outbreaks associated with fresh vegetables represent a growing problem for public health worldwide. In Argentina, Cryptosporidium spp., Toxoplasma gondii, Giardia spp. and Norovirus were reported in a risk ranking of foodborne pathogens transmitted by leafy green vegetables. In that sense, disinfection is a critical step in the processing of fresh vegetables to ensure their sanitization. The use of sodium hypochlorite solution as a disinfectant is very extended, but disadvantages like the generation of chlorine gas must be considered harmful for industry workers and consumers. The present study aimed to evaluate the parasite removal efficacy of two formulations of an industrial cleaner on fresh-cut vegetables contaminated with Taenia sp. eggs. Lettuce and broccoli were contaminated with Taenia sp. inocula and washed with ECOPAMPA® industrial cleaners (L1 and L2) through different assays, using distilled water as a control test. ECOPAMPA® (patent N° AR 119444 B1) was compounded by a non-ionic tensioactive and other ingredients of the Argentine Food Code. Comparison of the egg recovery between treatments showed that cleaners L1 and L2 resulted in a higher removal efficacy than distilled water in the washing of lettuce. Regarding broccoli, the superhydrophobicity of its cuticle could have affected the contamination with parasites. In that way, the recovery of parasite structures was low after washing with both cleaners and water. This study proposed the potential use of this industrial cleaner as an alternative treatment to remove parasite structures on fresh-cut vegetables.